The relative impact of brief treatment versus brief intervention in primary health‐care screening programs for substance use disorders. (February 2017) - Aldridge, Arnie; Dowd, William; Bray, Jeremy; Del Boca, Frances K.; Babor, Thomas F.; Bray, Jeremy W.
Abstract: Aims: To assess the relative impact of brief treatment (BT) compared with brief intervention (BI) on changes in substance use behavior in primary care screening programs for substance use disorders, overall and by patient severity. Design and participants: A total of 9029 patients with both baseline and follow‐up interviews were identified in the US Government Performance and Results Act (GPRA) data from October 2004 and February 2008. Using a propensity score framework, multiple generalized linear mixed models and a local linear matching method with a difference in difference estimator, patients from the BI group that resemble BT patients were used to determine the relative treatment effect of BT. A total of 3218 of these US patients with baseline and follow‐up interviews were used in the final analysis sample after the propensity score‐matching procedure (1448 patients assigned to a BI service category and 1770 assigned to a BT service category). Setting: United States. Measurements: Dependent variables were the number of days of use in the past 30 days of any alcohol, alcohol to intoxication, illicit drugs and marijuana. Findings: The relative impact of BT was not significant for alcohol (0.269; P  > 0.1) or alcohol to intoxication (0.462; P  > 0.1). BT was found to reduce the frequency of use of illicit drugs at follow‐up by 0.634 days more than BI ( P  < 0.05). Marijuana days were not affected significantly by assignment to BT (−0.128; P  > 0.1). Higher severity patients assigned to BT had a decrease in days of illicit drug use of 1.765 ( P  < 0.05). Conclusions: In the United States, brief treatment appears to have a stronger impact on reducing illicit drug use than brief intervention but is similar to brief intervention for reducing alcohol use, alcohol to intoxication and marijuana use alone.